FORMULATING EFFICIENT FRONTIER FROM CREDIT PORTFOLIO OF SENTRA KREDIT KECIL BANDUNG PT. BANK NEGARA INDONESIA AS A TOOL TO ANALYSE TO CREDIT COMPOSITION PLANNING - FAROLAN (NIM : 29106073); Pembimbing : Ir.Maryat Nirwandi, MBA, BONA
Bank faces many risks in doing its business; one of them is Credit Risk. Nowadays, banking in Indonesia still relies on credit as their main income, and also become the biggest risk for them. Therefore bank has always been forced to manage their credit portfolio in many ways to minimize the risk but still having regard to return can be granted. One of the tools to optimizing portfolio is with diversification as introduced by Prof. Harry Markowitz which known as Modern Portfolio Theory (MPT). Combination of any possible efficient portfolio is drawn in efficient frontier curve. In this theory, there are 3 (three) parameters that have to be resolved: Return, Risk and Correlation. In this final project, BNI Sentra Kredit Kecil (SKC) Bandung credit portfolio divided based on economic sector. Existing portfolio combination is Agriculture 0,864%, Mining 1,029%, Manufacturing 19,645%, Construction 21,205%, Trading 25,718%, Transportation, Warehousing and Communication 1,609%, Business Services 29,363% and Social service business 0,567%. This combination gives the portfolio expected return 0,367% pm and standard deviation 0,000270. From the extrapolation, concluded that existing portfolio is outside the efficient frontier curve, which mean the portfolio is not efficient. It produces less return with bigger risks. Ideally the portfolio composition is Agriculture 0.715%, Mining 0,00%, Manufacturing 52,409%, Construction 3,818%, Trading 22,175%, Transportation, Warehousing and Communication 0,888%, Business Services 19,995% and Social service business also has no part in this portfolio composition that is 0,00%. This portfolio will give return 0,450% pm and standard deviation of 0,000112. This calculation can be use as guidance to the management of BNI SKC Bandung to design its economic sector composition from its credit portfolio in order to meet the given target.